ICT literacy, resilience and online learning self-efficacy between Chinese rural and urban primary school students - Li, Jiaxin; Huang, Xinyi; Lei, Xinyu; Wen, Jiajie; Lu, Minghui (Frontiers in Psychology, 2022)
This study investigated the relationships between Chinese rural and urban primary school students’ information communications technology (ICT) literacy, student resilience, and online learning self-efficacy in a large-scale online education environment during the COVID-19 pandemic. We compared 5,040 primary school students in rural areas to 5,040 primary school students in urban areas with matching gender and grade in nine regions in the Guangdong–Hong Kong–Macao Greater Bay Area in mainland China, using a survey comprising an ICT literacy scale, a student resilience scale, an online learning self-efficacy scale, and an ICT devices scale. The ICT literacy, resilience and online learning self-efficacy of primary school students in rural areas were significantly lower than those of the control group (p<0.01). The primary school students’ ICT literacy was significantly associated with student resilience and online learning self-efficacy. Student resilience played a mediating role between ICT literacy and online learning self-efficacy, while the rural/urban area factor moderated the relationship between ICT literacy and student resilience. These findings suggest that ICT literacy is more scarce and important for primary school students in rural areas of China than for those in urban areas. Improving ICT literacy among primary school students can enhance students’ resilience and thus improve their online learning self-efficacy, especially in rural areas.